Management of bovine brucellosis in organized dairy herds through the identification of risk factors: A cross-sectional study from Karnataka, India - Shome, R.; Natesan, K.; Kalleshamurthy, T.; Yadav, C.; Sahay, S.; Skariah, S.; Mohandoss, N.; Kumar, O.R.V.; Shome, B.R.; Rahman, Habibar (Veterinary World, 2023)
Background and Aim: Brucellosis is an infectious disease caused by Brucella species. This study aimed to identify the risk factors associated with bovine brucellosis seropositivity in organized dairy farms to control the disease in unvaccinated adult bovine herds in Karnataka, India.